Penerapan Data Mining Pada Transaksi Penjualan Barang Menggunakan Metode Apriori (Studi Kasus:Toko BE-MART) - Feny Rosalina Pare; Olfiana Wati; Leni Paula Taran; Lidia Maria Arsai (Universitas Islam Raden Rahmat, Malang, 2023)
The development of data in the digital era is very important, because data is likened to a resource that can produce new information or knowledge. The process of selling/purchasing goods at BE-MART is carried out every day, so the layout of the goods is carried out according to the sales pattern. By processing the data, adjustments to sales of goods can be made. To catch this problem, there are several solutions offered, one of which is a data mining technique by analyzing goods sales transaction data. What items are usually purchased by customers together or also known as the a priori method. The results of the study have shown that data mining is very useful for knowing the relationship between the frequency pattern of sales of basic needs and the daily needs that are most often purchased by consumers. Relationship patterns that have become product information are usually sold together with the sale of other products that are useful for providing strategic marketing proposals for the store. The results obtained are that if consumers buy softex, they will buy skincare and produce a support value of 0.011% and a confidence of 1%.